Phosphorus Efficiency Mechanisms of Two Wheat Cultivars as Affected by a Range of Phosphorus Levels in the Field - Deng, Yan; Teng, Wan; Tong, Yi-Ping; Chen, Xin-Ping; Zou, Chun-Qin (Frontiers in Plant Science, 2018)
Phosphorus (P) efficiency includes both P acquisition efficiency (PAE) and internal P utilization efficiency (PUE). Despite substantial research, genotypic variation in PAE and PUE remains incompletely understood in the field. A 2-year field study was conducted to compare PAE and PUE and related morphological, physiological, and molecular root traits of two winter wheat cultivars (Triticum aestivum L. cv. SJZ8 and KN92) in response to six P application rates in a P-deficient calcareous soil. Both cultivars showed similar growth and yield potential at each P supply level, reaching optimal growth at the same P application rate of about 100 kg P ha-1. However, the two cultivars differed in how they achieved yield and P efficiency. As P supply increased for both cultivars, root dry weight (RDW), root length density, and expression of the phosphate transporter gene TaPHT1.2 in roots initially increased and then stabilized, but arbuscular mycorrhizal fungal colonization, rhizosphere acid phosphatase activity, expressions of the P-starvation marker gene TaIPS1.1 and the purple acid phosphatase gene TaPAP16 in roots initially decreased and then stabilized. To enhance P acquisition when the P supply was deficient, KN92 modified the morphology of its roots, while SJZ8 increased the physiological activities in its roots. With an adequate P supply, high expression of TaPHT1.2 in roots might account for efficient P uptake for both cultivars, especially for KN92. Although P uptake per RDW was similar for both cultivars at anthesis, PAE was higher for KN92 than SJZ8 in terms of total P uptake in aboveground parts, whereas shoot and grain PUE were higher in SJZ8 than in KN92, mainly during the reproductive growth stage. These results indicate that P efficiency is under genotypic control at all P supply levels tested in both wheat cultivars, and that the two cultivars depend on different root strategies for P acquisition and utilization in response to changes in the P supply.